A kind of aging-resistant low-viscosity high-thermal-conductivity polyurethane adhesive and preparation method thereof
By using anti-aging agents to modify thermal conductive powder and silane-modified anti-aging agents in polyurethane adhesives, the problems of high viscosity, poor bonding performance and insufficient aging resistance of thermally conductive polyurethane adhesives are solved, and the effects of reducing viscosity, improving bonding strength and aging resistance are achieved.
Patent Information
- Application Number
- CN202411968539.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
AI Technical Summary
The existing thermally conductive polyurethane adhesives have problems such as excessive viscosity, poor adhesive performance and insufficient aging resistance.
By using anti-aging agents to modify thermal conductive powders and silane-modified anti-aging agents in components A and B, the moisture-heat aging resistance of polyurethane adhesives and compatibility with resins are improved, and the system viscosity is reduced.
It achieves reducing viscosity, improving adhesive strength and aging resistance, and significantly improving the service life and safety of the adhesive.
Smart Images

Figure BDA0005218956490000121
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer material preparation, in particular to an aging-resistant, low-viscosity, high-thermal-conductivity polyurethane adhesive, which can be applied to the modification of fillers and the production of polyurethane adhesives. Background Art
[0002] At present, new energy, electronic appliances and other fields are facing the problem of heat accumulation. Thermal conductive polyurethane adhesives have excellent high and low temperature performance, unique soft and hard segment structure that is easy to modify, high bonding strength and other performance characteristics. They are widely used, especially in the fields of power battery PACK, energy storage battery PACK, etc. Thermal conductive adhesives are mostly polyurethane type.
[0003] However, there are several problems with thermally conductive polyurethane adhesives: First, high filling levels of thermally conductive fillers make the viscosity of polyurethane adhesives too high; second, the compatibility of fillers and resins is poor, resulting in poor bonding performance; third, urethane bonds are easily hydrolyzed, resulting in poor wet heat aging performance.
[0004] The conventional modification method of thermal conductive fillers is to improve the compatibility with the resin by esterification reaction of the hydroxyl groups on the surface of the fillers or hydrolysis condensation with coupling agents, but the bonding performance will still decrease and the aging resistance is poor. Adding antioxidants is an effective way to improve the wet heat aging performance of polyurethane adhesives, but if they are only added through physical blending, small molecule antioxidants will migrate or even precipitate as the use time increases or in high temperature and high humidity environments, resulting in reduced bonding strength.
[0005] In summary, how to develop a thermally conductive filler and an aging-resistant, low-viscosity, high-thermal-conductivity polyurethane adhesive that has the advantages of reducing viscosity, improving compatibility, enhancing adhesion, and being resistant to moisture and heat aging is an urgent problem to be solved.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The purpose of the present invention is to provide an aging-resistant, low-viscosity, high-thermal-conductive polyurethane adhesive and a preparation method thereof, which has low raw material price, simple modification method, and excellent aging-resistant performance, and can well solve the technical problems of existing thermal-conductive polyurethane adhesives such as high viscosity, low bonding strength, and poor aging-resistant performance.
[0008] The present invention is achieved through the following technical solutions:
[0009] An aging-resistant, low-viscosity, high-thermal-conductivity polyurethane adhesive and a preparation method thereof, comprising:
[0010] Component A and component B, wherein component A and component B are used in a volume ratio of 1:1, and the functional group molar ratio is: NCO:OH=1.02:1-2.0:1;
[0011] The component A is made of the following materials in parts by mass: 0.1 to 15 parts of bio-based polyol, 0.1 to 5 parts of aromatic ring modified polyol, 0.1 to 10 parts of polyether polyol, 0.001 to 0.1 parts of catalyst, 0.1 to 5 parts of molecular sieve, 0.1 to 85 parts of common modified thermal conductive powder and 0.1 to 85 parts of antioxidant modified thermal conductive powder;
[0012] The component B is made of the following components in parts by mass: 15-35 parts of terminal isocyanate polyurethane prepolymer, 0.1-1 part of water absorbent, 0.1-85 parts of common modified thermal conductive powder, 0.1-85 parts of antioxidant modified thermal conductive powder and 0.1-1 part of silane modified antioxidant.
[0013] Preferably, in the above adhesive, in the component A and the component B, the antioxidant modified thermal conductive powder is prepared in the following manner, and each component, by weight, comprises:
[0014] Weigh 100 parts of unmodified thermal conductive powder, dry it and place it in a high-speed disperser;
[0015] Weigh 100 parts of silane modified antioxidant for pre-hydrolysis and dissolve in a low boiling point solvent to prepare a solution with a mass concentration of 20-99%, then weigh 0.001-5 parts of the solution and slowly disperse it in the unmodified thermal conductive powder, heat to 40-130° C. and react for 0.1-12 hours, then remove the water and low boiling point solvent in vacuum to obtain the antioxidant modified thermal conductive powder.
[0016] Preferably, in the above adhesive, the low boiling point solvent is an alcohol solvent or an ester solvent, the alcohol solvent is one or more of ethanol, methanol, and isopropanol; and the ester solvent is ethyl acetate.
[0017] Preferably, in the above adhesive, in the component A and the component B, the silane-modified antioxidant is prepared in the following manner, and each component, measured by weight, comprises:
[0018] Weigh 100 parts of hindered phenol antioxidant, add 0.01-0.3 parts of Lewis acid catalyst, heat to 40-100°C, slowly drop acryloyl chloride, react for 1-12 hours until the reaction is finished, and obtain a vinyl-terminated antioxidant. Weigh 100 parts of vinyl-terminated antioxidant according to the molar ratio of vinyl-terminated antioxidant: acryloyl chloride = 1.002-1.3, add alkyl silane coupling agent to the vinyl-terminated antioxidant, and then add 0.01-1000 ppm of platinum catalyst, react at 50-120°C for 5-48 hours to obtain a silane-modified antioxidant. In the silane-modified antioxidant, the molar ratio of vinyl-terminated antioxidant: alkyl silane coupling agent = 1:0.9-1.1.
[0019] Preferably, in the above adhesive, in the silane-modified antioxidant, the hindered phenol antioxidant is one or more antioxidants containing phenol groups;
[0020] The Lewis acid catalyst is AlCl 3 , BF 3 、SbCl 5 , FeBr 3 、FeCl 3 SnCl 4 、TiCl 4 、ZnCl 2 At least one of;
[0021] The alkylsilane coupling agent is one or more of a methylsilane coupling agent, an ethylsilane coupling agent, and an octylsilane coupling agent.
[0022] Preferably, in the above adhesive, the antioxidant containing a phenol group is any one of antioxidant 1076, antioxidant 1330, antioxidant 1135, antioxidant 2103 or a blend thereof.
[0023] Preferably, in the above adhesive, in the component A, the bio-based polyol is castor oil, modified castor oil, soybean oil, modified soybean oil, cashew nut shell oil, cardanol polyol or a blend thereof, and has a molecular weight of 200 to 5000;
[0024] The aromatic ring modified polyol is any one of aromatic ring modified polyether polyol, aromatic ring modified polyester polyol, aromatic ring modified bio-based polyol or a blend thereof, and has a molecular weight of 200 to 5000.
[0025] The polyether polyol is any one of polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polypropylene glycol, or a blend thereof, and has a molecular weight of 200 to 5000;
[0026] The catalyst is any one of bismuth isooctanoate, bismuth laurate, bismuth neodecanoate, bismuth naphthenate, zinc isooctanoate, zinc neodecanoate, dibutyltin, stannous octoate, chelated tin, or a blend thereof;
[0027] The molecular sieve is any one of 3A molecular sieve activated powder, 4A molecular sieve activated powder, 5A molecular sieve activated powder or a blend thereof;
[0028] The common modified thermal conductive powder material adopts any one of aluminum hydroxide, modified aluminum oxide, modified heavy calcium, modified calcium hydrogen, modified nano calcium, modified silicon micro powder or a blend thereof modified by a silane coupling agent or an esterification reaction.
[0029] Preferably, in the above-mentioned adhesive, in the component B, the terminal isocyanate-based polyurethane prepolymer is prepared in the following manner, and each component is measured by weight, including: heating the polyol to 110-130°C, stirring and vacuuming, dehydrating for 1-3 hours, cooling to below 50°C, filling with nitrogen, adding isocyanate at a ratio of 6-20% of the theoretical NCO content, heating to 65-85°C, stirring and reacting for 1-4 hours, until the titrated NCO content no longer changes to terminate the reaction, and cooling to room temperature to obtain the terminal isocyanate-based polyurethane prepolymer.
[0030] Preferably, in the above adhesive, in the isocyanate-terminated polyurethane prepolymer, the polyol is any one of polyether polyol, polyester polyol, bio-based polyol or a blend thereof;
[0031] The isocyanate may be any one of aliphatic isocyanate and aromatic isocyanate or a blend thereof.
[0032] A method for preparing the aging-resistant, low-viscosity, and high-thermal-conductivity polyurethane adhesive of the present invention comprises:
[0033] Prepare component A and component B respectively;
[0034] Preparation of component A:
[0035] Take the raw materials used for component A according to the formula of the present invention;
[0036] The bio-based polyol, aromatic ring modified polyol, polyether polyol, catalyst, molecular sieve, common modified thermal conductive powder and antioxidant modified thermal conductive powder in the raw materials of component A are mixed uniformly in a reaction kettle to obtain component A;
[0037] Preparation of component B:
[0038] Take the raw materials used for component B according to the formula of the present invention;
[0039] The isocyanate-terminated polyurethane prepolymer, water absorbent, common modified thermal conductive powder, antioxidant modified thermal conductive powder and silane modified antioxidant in the raw materials of component B are mixed uniformly in a reaction kettle to obtain component B;
[0040] The component A and the component B prepared above are used in a volume ratio of 1:1 to obtain an aging-resistant, low-viscosity, and high-thermal-conductivity polyurethane adhesive;
[0041] The antioxidant modified thermal conductive powder used in the A component and the B component is prepared in the following manner, with each component being calculated by weight, comprising: weighing 100 parts of unmodified thermal conductive powder, drying it, and placing it in a high-speed disperser;
[0042] Weigh 100 parts of silane modified antioxidant for pre-hydrolysis and dissolve in a low boiling point solvent to prepare a solution with a mass concentration of 20-99%, then weigh 0.001-5 parts of the solution and slowly disperse it in the unmodified thermal conductive powder, heat to 40-130° C. and react for 0.1-12 hours, then remove water and low boiling point solvent in vacuum to obtain antioxidant modified thermal conductive powder;
[0043] The silane-modified antioxidant used in the component A and the component B is prepared in the following manner, wherein each component is measured by weight, including: weighing 100 parts of a hindered phenol antioxidant, adding 0.01 to 0.3 parts of a Lewis acid catalyst, heating to 40 to 130° C., slowly dropping acryloyl chloride, reacting for 1 to 12 hours before the reaction is completed to obtain a vinyl-terminated antioxidant, weighing 100 parts of the vinyl-terminated antioxidant according to a molar ratio of the vinyl-terminated antioxidant to acryloyl chloride of 1.002 to 1.3, adding an alkyl silane coupling agent to the vinyl-terminated antioxidant, and then adding 0.01 to 1000 ppm of a platinum catalyst, reacting at 50 to 120° C. for 5 to 48 hours to obtain a silane-modified antioxidant, wherein the molar ratio of the vinyl-terminated antioxidant to the alkyl silane coupling agent is 1:0.9 to 1.1;
[0044] The terminal isocyanate polyurethane prepolymer used in the B component is prepared in the following manner, with each component measured by weight, including: heating the polyol to 110-130° C., stirring and evacuating, dehydrating for 1-3 hours, cooling to below 50° C., filling with nitrogen, adding isocyanate at a ratio of 6-20% of the theoretical NCO content, heating to 65-85° C., stirring and reacting for 1-4 hours, until the titrated NCO content no longer changes, ending the reaction, and cooling to room temperature to obtain the terminal isocyanate polyurethane prepolymer.
[0045] Compared with the prior art, the aging-resistant, low-viscosity, high-thermal-conductivity polyurethane adhesive and its preparation method provided by the present invention have the following beneficial effects when the addition amount of the conventional modified thermally conductive filler and the antioxidant is the same:
[0046] By using antioxidant modified thermal conductive powder in component A, and antioxidant modified thermal conductive powder and silane modified antioxidant in component B, not only can the wet heat aging resistance and compatibility with resin be improved, but also the polarity can be increased and the adhesion with substrate can be enhanced. In addition, the silane modified antioxidant can also be used as an adhesion promoter to improve the bonding performance. It has the advantages of low raw material price, simple modification method, excellent aging resistance and the like. After using the adhesive of the aging-resistant modified thermal conductive filler of the present invention, the viscosity is reduced from 250000 to 190000cps, and the viscosity is significantly reduced; the shear strength is increased from 6MPa to 8.5MPa, and the bonding performance is significantly improved; the tensile and shear performance attenuation rate after double 85 wet heat aging for 1000h is reduced from 30% to less than 10%, and the aging resistance is greatly improved. DETAILED DESCRIPTION
[0047] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in combination with the specific content of the present invention; it is obvious that the described embodiments are only part of the embodiments of the present invention, not all of the embodiments, which does not constitute a limitation of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the protection scope of the present invention.
[0048] First, the terms that may be used in this article are explained as follows:
[0049] The term “and / or” means that either or both of them can be realized at the same time. For example, X and / or Y means both “X” or “Y” and “X and Y”.
[0050] The terms "include", "comprises", "contains", "has" or other descriptions with similar semantics should be interpreted as non-exclusive inclusion. For example, including certain technical feature elements (such as raw materials, components, ingredients, carriers, dosage forms, materials, dimensions, parts, components, mechanisms, devices, steps, procedures, methods, reaction conditions, processing conditions, parameters, algorithms, signals, data, products or products, etc.) should be interpreted as including not only certain technical feature elements explicitly listed, but also other technical feature elements known in the art that are not explicitly listed.
[0051] The term "consisting of..." means excluding any technical feature elements not explicitly listed. If this term is used in a claim, it will make the claim closed, so that it does not contain technical feature elements other than the technical feature elements explicitly listed, except for the conventional impurities related to them. If this term only appears in a clause of a claim, it only limits the elements explicitly listed in the clause, and the elements recorded in other clauses are not excluded from the overall claim.
[0052] The term "parts by mass" refers to the mass ratio relationship between multiple components. For example, if it is described that component X is x parts by mass and component Y is y parts by mass, then the mass ratio of component X to component Y is x:y. 1 part by mass can represent any mass, for example, 1 part by mass can be represented as 1 kg or 3.1415926 kg. The sum of the parts by mass of all components is not necessarily 100 parts, but can be greater than 100 parts, less than 100 parts or equal to 100 parts. Unless otherwise specified, the parts, proportions and percentages described herein are all measured by mass.
[0053] When concentration, temperature, pressure, size or other parameters are expressed in the form of a numerical range, the numerical range should be understood to specifically disclose all ranges formed by the pairing of any upper limit, lower limit, and preferred value in the numerical range, regardless of whether the range is explicitly stated; for example, if a numerical range of "2 to 8" is stated, the numerical range should be interpreted as including ranges such as "2 to 7", "2 to 6", "5 to 7", "3 to 4 and 6 to 7", "3 to 5 and 7", "2 and 5 to 7", etc. Unless otherwise specified, the numerical ranges stated herein include both their end values and all integers and fractions within the numerical range.
[0054] The high barrier heat-resistant solvent-free polyurethane composite material and the preparation method thereof provided by the present invention are described in detail below. The contents not described in detail in the embodiments of the present invention belong to the prior art known to professional and technical personnel in the field. If no specific conditions are specified in the embodiments of the present invention, the conventional conditions in the field or the conditions recommended by the manufacturer are followed. The reagents or instruments used in the embodiments of the present invention, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0055] The embodiment of the present invention provides an aging-resistant, low-viscosity, and high-thermal-conductive polyurethane adhesive, comprising:
[0056] Component A and component B, wherein component A and component B are used in a volume ratio of 1:1, and the functional group molar ratio of component A to component B is: NCO:OH=1.02:1-2.0:1;
[0057] Calculated by mass ratio, the component A is composed of the following materials: 0.1 to 15 parts of bio-based polyol, 0.1 to 5 parts of aromatic ring modified polyol, 0.1 to 10 parts of polyether polyol, 0.001 to 0.1 parts of catalyst, 0.1 to 5 parts of molecular sieve, 0.1 to 85 parts of common modified thermal conductive powder and 0.1 to 85 parts of antioxidant modified thermal conductive powder;
[0058] The component B is made of the following components: 15-35 parts of terminal isocyanate polyurethane prepolymer, 0.1-1 part of water absorbent, 0.1-85 parts of common modified thermal conductive powder, 0-85 parts of antioxidant modified thermal conductive powder and 0.1-1 part of silane modified antioxidant.
[0059] Preferably, in component A of the above adhesive, the bio-based polyol is any one of castor oil, modified castor oil, soybean oil, modified soybean oil, cashew nut shell oil, and cardanol polyol, or a blend thereof, and has a molecular weight between 200 and 5000.
[0060] Preferably, in component A of the above adhesive, the aromatic ring modified polyol is any one of aromatic ring modified polyether polyol, aromatic ring modified polyester polyol, aromatic ring modified bio-based polyol or a blend thereof, and has a molecular weight between 200 and 5000.
[0061] Preferably, in component A of the adhesive, the polyether polyol is any one of polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polypropylene glycol, or a blend thereof, and has a molecular weight between 200 and 5000.
[0062] Preferably, in component A of the above adhesive, the catalyst is any one of bismuth isooctanoate, bismuth laurate, bismuth neodecanoate, bismuth cyclopentaneate, zinc isooctanoate, zinc neodecanoate, dibutyltin, stannous octoate, chelated tin, or a blend thereof.
[0063] Preferably, in component A of the above adhesive, the molecular sieve is any one of 3A molecular sieve activated powder, 4A molecular sieve activated powder, 5A molecular sieve activated powder or a blend thereof.
[0064] Preferably, in component A of the adhesive, the common modified thermal conductive powder is any one of aluminum hydroxide, modified aluminum oxide, modified heavy calcium, modified calcium hydrogen, modified nano calcium, modified silicon micropowder modified by silane coupling agent or esterification reaction, or a blend thereof.
[0065] Preferably, in the components A and B of the above-mentioned adhesive, the antioxidant modified thermal conductive powder is prepared according to the following steps (the amount of each component is in parts by weight): 100 parts of unmodified thermal conductive powder are weighed, dried and placed in a high-speed disperser, 100 parts of silane-modified antioxidant are weighed for pre-hydrolysis, and dissolved in low-boiling point solvents such as alcohols (ethanol, methanol, isopropanol, etc.) and esters (ethyl acetate, etc.) to form a solution with a mass concentration of 20-99%, and then 0.001-5 parts of the solution are weighed and slowly dispersed in the dispersed unmodified thermal conductive powder, the temperature is raised to 40-130°C and the reaction is carried out for 0.1-12 hours, and then the moisture, solvent, etc. are removed in vacuo to obtain the antioxidant modified thermal conductive powder.
[0066] Preferably, the thermally conductive powder is one or more of aluminum hydroxide, aluminum oxide, heavy calcium, calcium hydrogen, nano calcium, and silicon micropowder.
[0067] Preferably, in component B of the above-mentioned adhesive, the silane-modified antioxidant comprises the following steps (the amount of each component is in parts by weight): weigh 100 parts of hindered phenol antioxidant, add 0.01-0.3 parts of Lewis acid catalyst, heat to 40-100°C, slowly add acryloyl chloride, react for 1-12 hours and then terminate the reaction to obtain a vinyl-terminated antioxidant, the molar ratio of antioxidant: acryloyl chloride = 1.002-1.3; weigh 100 parts of vinyl-terminated antioxidant, add alkyl silane coupling agent (methyl, ethyl, octyl, etc.), add 0.01-1000 ppm of platinum catalyst, react at 50-120°C for 5-48 hours to obtain a silane-modified antioxidant, in which the molar ratio of vinyl-terminated antioxidant: alkyl silane coupling agent = 1:0.9-1.1.
[0068] In the preparation of the silane-modified antioxidant, the hindered phenol antioxidant used includes an antioxidant containing a phenol group, such as antioxidants containing phenol groups of grades 1076, 1330, 1135, 2103 or blends thereof.
[0069] The Lewis acid catalysts used include AlCl 3 , BF 3 、SbCl 5 , FeBr 3 、FeCl 3 SnCl 4 、TiCl 4 、ZnCl 2 wait.
[0070] Preferably, in component B of the above-mentioned adhesive, the terminal isocyanate polyurethane prepolymer is prepared according to the following steps (the amount of each component is in parts by weight): the polyol is heated to 110-130°C, stirred and vacuumed, dehydrated for 1-3 hours, cooled to below 50°C, filled with nitrogen, and isocyanate is added at a ratio of 6-20% of the theoretical NCO content, heated to 65-85°C, and stirred for 1-4 hours until the titrated NCO content no longer changes to terminate the reaction, and cooled to room temperature to obtain a terminal isocyanate polyurethane prepolymer.
[0071] Preferably, in the preparation of the isocyanate-terminated polyurethane prepolymer, the polyol used is any one of polyether polyol, polyester polyol, bio-based polyol or a blend thereof.
[0072] The isocyanate used may be any of aliphatic isocyanate and aromatic isocyanate or a blend thereof.
[0073] The embodiment of the present invention also provides a method for preparing an aging-resistant, low-viscosity, and high-thermal-conductivity polyurethane adhesive, comprising the following steps:
[0074] Prepare component A and component B respectively, wherein:
[0075] Preparation of component A:
[0076] According to the above-mentioned formula of component A, take all the raw materials used and mix them evenly to prepare component A;
[0077] Preparation of component B:
[0078] According to the above B component formula, take all the raw materials used and mix them evenly to prepare B component;
[0079] The component A and the component B prepared above are mixed in a volume ratio of 1:1 to obtain an aging-resistant, low-viscosity, and high-thermal-conductivity polyurethane adhesive.
[0080] In summary, in the aging-resistant low-viscosity high-thermal-conductive polyurethane adhesive of the present invention, a vinyl-terminated antioxidant is obtained by modifying a hindered phenol antioxidant with acryloyl chloride, and then a silane-modified antioxidant is obtained by a silane-hydrogenation reaction with an alkylsilane coupling agent. The antioxidant is used to undergo hydrolysis and condensation with the hydroxyl group of the thermal conductive filler to finally obtain an aging-resistant modified thermal conductive powder. The hindered phenol antioxidant can undergo an acylation reaction with the acyl chloride, and then a Fres rearrangement is performed to obtain a terminal allyl antioxidant. The allyl group undergoes a silane-hydrogenation reaction with the alkylsilane coupling agent to obtain a silane-modified antioxidant. After the coupling agent is hydrolyzed, a condensation reaction occurs with the hydroxyl group on the surface of the thermal conductive powder to obtain an aging-resistant modified thermal conductive powder. Not only does it solve the problem of precipitation of the antioxidant and improve the aging resistance, but it can also effectively improve the compatibility of the thermal conductive powder with the resin, reduce the viscosity of the system, and effectively improve the interaction between the adhesive and the substrate, which is comprehensively manifested as improved aging resistance, reduced viscosity, and improved bonding strength.
[0081] In order to more clearly demonstrate the technical solution and technical effects provided by the present invention, an aging-resistant, low-viscosity, high-thermal-conductive polyurethane adhesive and a preparation method thereof provided by an embodiment of the present invention are described in detail with reference to specific embodiments below.
[0082] Embodiment 1:
[0083] This embodiment provides an aging-resistant, low-viscosity, high-thermal-conductivity polyurethane adhesive, and its preparation method is as follows (the amount of each raw material component is part by weight):
[0084] (1) Preparation of common silane-modified thermally conductive aluminum hydroxide powder, i.e. preparation of common modified thermally conductive powder:
[0085] Weigh 100 parts of unmodified aluminum hydroxide powder, dry them and place them in a high-speed disperser, weigh 1 part of KH560 for pre-hydrolysis, and dissolve it in isopropanol to make an 80% solution, then slowly disperse the solution in the powder, heat to 70°C and react for 4 hours, then vacuum remove moisture, solvent, etc. to obtain ordinary silane-modified thermally conductive aluminum hydroxide powder.
[0086] (2) Preparation of isocyanate-terminated polyurethane prepolymer:
[0087] Take 35 parts of polypropylene glycol with a molecular weight of 2000, stir and heat to 110°C, maintain vacuum to remove water for 3 hours, cool to 40°C, fill with nitrogen, add 65 parts of liquefied MDI, slowly heat to 75°C, stir to react for 2.5 hours, cool to room temperature to obtain a terminal isocyanate polyurethane prepolymer.
[0088] (3) Preparation of component A (the amount of each component is in parts by weight): 4.5 parts of castor oil polyol, 2.5 parts of bisphenol A polyether polyol, 2 parts of polypropylene glycol with a molecular weight of 1000, 11 parts of modified castor oil (Ito AC009), 80 parts of ordinary silane-modified thermal conductive aluminum hydroxide powder, 0.002 parts of dibutyltin dilaurate and 0.6 parts of 1076 were mixed, dispersed and stirred evenly, and component A was obtained after stirring for 2 hours;
[0089] (4) Preparation of component B (the amount of each component is in parts by weight): 20 parts of isocyanate-terminated polyurethane prepolymer and 80 parts of ordinary silane-modified thermally conductive aluminum hydroxide powder are mixed and stirred for 2 hours to obtain component B;
[0090] The component A and component B prepared above are mixed in a volume ratio of 1:1 to obtain the aging-resistant, low-viscosity, and high-thermal-conductive polyurethane adhesive of this embodiment.
[0091] Embodiment 2:
[0092] This embodiment provides an aging-resistant, low-viscosity, high-thermal-conductivity polyurethane adhesive, and its preparation method is as follows (the amount of each raw material component is part by weight):
[0093] (1) Preparation of silane-modified antioxidant:
[0094] Weigh 100 parts of antioxidant 1076 and dissolve it in ethyl acetate. Weigh 0.1 parts of AlCl 3 The catalyst was stirred evenly, and 16.7 parts of acryloyl chloride was slowly added dropwise while stirring. After heating to 45°C for 3 hours, the pH was adjusted to neutral, washed with water, filtered, and vacuum dried to obtain the vinyl-terminated 1076. Weigh 100 parts of vinyl-terminated 1076, add 31 parts of methyltriethoxysilane coupling agent, add 0.05 parts of chloroplatinic acid catalyst, heat to 80°C for 20 hours, and obtain silane-modified antioxidant 1076.
[0095] (2) Preparation of antioxidant-modified thermally conductive aluminum hydroxide powder, i.e. preparation of antioxidant-modified thermally conductive powder:
[0096] Weigh 100 parts of unmodified aluminum hydroxide powder, dry and place in a high-speed disperser, weigh 2 parts of silane-modified antioxidant for pre-hydrolysis, and dissolve in isopropanol to form an 80% solution, then slowly disperse the solution in the powder, heat to 70°C and react for 4 hours, then vacuum remove moisture, solvent, etc. to obtain antioxidant-modified thermally conductive aluminum hydroxide powder.
[0097] (3) Preparation of isocyanate-terminated polyurethane prepolymer:
[0098] Take 35 parts of polypropylene glycol with a molecular weight of 2000, stir and heat to 110°C, maintain vacuum to remove water for 3 hours, cool to 40°C, fill with nitrogen, add 65 parts of liquefied MDI, slowly heat to 75°C, stir to react for 2.5 hours, cool to room temperature to obtain a terminal isocyanate polyurethane prepolymer.
[0099] (4) Preparation of component A (the amount of each component is in parts by weight): 4.5 parts of castor oil polyol, 2.5 parts of bisphenol A polyether polyol, 2 parts of polypropylene glycol with a molecular weight of 1000, 11 parts of modified castor oil (Ito AC009), 80 parts of antioxidant modified thermal conductive aluminum hydroxide powder and 0.002 parts of dibutyltin dilaurate are mixed, dispersed and stirred evenly, and component A is obtained after stirring for 2 hours;
[0100] (5) Preparation of component B (the amount of each component is in parts by weight): 20 parts of isocyanate-terminated polyurethane prepolymer and 80 parts of antioxidant-modified thermally conductive aluminum hydroxide powder are mixed and stirred for 2 hours to obtain component B;
[0101] The component A and component B prepared above are mixed in a volume ratio of 1:1 to obtain the aging-resistant, low-viscosity, and high-thermal-conductivity polyurethane adhesive of this embodiment.
[0102] Embodiment 3:
[0103] This embodiment provides an aging-resistant, low-viscosity, high-thermal-conductivity polyurethane adhesive, and its preparation method is as follows (the amount of each raw material component is part by weight):
[0104] (1) Preparation of silane-modified antioxidant:
[0105] Weigh 100 parts of antioxidant 1135 and dissolve it in ethyl acetate. Weigh 0.07 parts of AlCl 3The catalyst was stirred evenly, and 16 parts of acryloyl chloride was slowly added dropwise while stirring. After heating to 40°C for 2 hours, the pH was adjusted to neutral, washed with water, filtered, and vacuum dried to obtain the vinyl-terminated 1135. Weigh 100 parts of vinyl-terminated 1135, add 35 parts of ethyltriethoxysilane coupling agent, add 0.06 parts of chloroplatinic acid catalyst, heat to 75°C for 20 hours, and obtain silane-modified antioxidant 1135.
[0106] (2) Preparation of thermally conductive aluminum hydroxide powder modified by antioxidant 1135, i.e. preparation of thermally conductive powder modified by antioxidant:
[0107] Weigh 100 parts of unmodified aluminum hydroxide powder, dry and place in a high-speed disperser, weigh 2 parts of silane-modified antioxidant for pre-hydrolysis, and dissolve in isopropanol to form an 80% solution, then slowly disperse the solution in the powder, heat to 70°C and react for 4 hours, then vacuum remove moisture, solvent, etc. to obtain antioxidant-modified thermally conductive aluminum hydroxide powder.
[0108] (3) Preparation of isocyanate-terminated polyurethane prepolymer:
[0109] Take 35 parts of polypropylene glycol with a molecular weight of 2000, stir and heat to 110°C, maintain vacuum to remove water for 3 hours, cool to 40°C, fill with nitrogen, add 65 parts of liquefied MDI, slowly heat to 75°C, stir to react for 2.5 hours, cool to room temperature to obtain a terminal isocyanate polyurethane prepolymer.
[0110] (4) Preparation of component A: 4.5 parts of castor oil polyol, 2.5 parts of bisphenol A polyether polyol, 2 parts of polypropylene glycol with a molecular weight of 1000, 11 parts of modified castor oil (Ito AC009), 80 parts of antioxidant modified thermal conductive aluminum hydroxide powder and 0.002 parts of dibutyltin dilaurate were mixed, dispersed and stirred evenly, and stirred for 2 hours to obtain component A;
[0111] (5) Preparation of component B: 20 parts of isocyanate-terminated polyurethane prepolymer and 80 parts of antioxidant-modified thermally conductive aluminum hydroxide powder were mixed and stirred for 2 hours to obtain component B;
[0112] The component A and component B prepared above are mixed in a volume ratio of 1:1 to obtain the aging-resistant, low-viscosity, and high-thermal-conductivity polyurethane adhesive of this embodiment.
[0113] Embodiment 4:
[0114] This embodiment provides an aging-resistant, low-viscosity, high-thermal-conductivity polyurethane adhesive, and its preparation method is as follows (the amount of each raw material component is part by weight):
[0115] (1) Preparation of silane-modified antioxidant:
[0116] Weigh 100 parts of antioxidant 1135 and dissolve it in ethyl acetate. Weigh 0.07 parts of AlCl 3 The catalyst was stirred evenly, and 16 parts of acryloyl chloride was slowly added dropwise while stirring. After heating to 40°C for 2 hours, the pH was adjusted to neutral, washed with water, filtered, and vacuum dried to obtain the vinyl-terminated 1135. Weigh 100 parts of vinyl-terminated 1135, add 35 parts of ethyltriethoxysilane coupling agent, add 0.06 parts of chloroplatinic acid catalyst, heat to 75°C for 20 hours, and obtain silane-modified antioxidant 1135.
[0117] (2) Preparation of thermally conductive aluminum hydroxide powder modified by antioxidant 1135, i.e. preparation of thermally conductive powder modified by antioxidant:
[0118] Weigh 100 parts of unmodified aluminum hydroxide powder, dry and place in a high-speed disperser, weigh 2 parts of silane-modified antioxidant for pre-hydrolysis, and dissolve in isopropanol to form an 80% solution, then slowly disperse the solution in the powder, heat to 70°C and react for 4 hours, then vacuum remove moisture, solvent, etc. to obtain antioxidant-modified thermally conductive aluminum hydroxide powder.
[0119] (3) Preparation of isocyanate-terminated polyurethane prepolymer:
[0120] Take 30 parts of poly(hexamethylene dimer) diol with a molecular weight of 2000, heat to 110°C while stirring, keep vacuuming to remove water for 2 hours, cool to 40°C, fill with nitrogen, add 70 parts of liquefied MDI, slowly heat to 75°C, stir to react for 2 hours, and cool to room temperature to obtain a terminal isocyanate polyurethane prepolymer.
[0121] (4) Preparation of component A: 6 parts of castor oil polyol, 4 parts of bisphenol A polyether polyol, 10 parts of modified castor oil (Ito AC006), 80 parts of antioxidant modified thermal conductive aluminum hydroxide powder and 0.002 parts of dibutyltin dilaurate were mixed, dispersed and stirred evenly, and component A was obtained after stirring for 2 hours;
[0122] (5) Preparation of component B: 20 parts of isocyanate-terminated polyurethane prepolymer and 80 parts of antioxidant-modified thermally conductive aluminum hydroxide powder were mixed and stirred for 2 hours to obtain component B;
[0123] The component A and component B prepared above are mixed in a volume ratio of 1:1 to obtain the aging-resistant, low-viscosity, and high-thermal-conductive polyurethane adhesive of this embodiment.
[0124] Embodiment 5:
[0125] This embodiment provides an aging-resistant, low-viscosity, high-thermal-conductivity polyurethane adhesive, and its preparation method is as follows (the amount of each raw material component is part by weight):
[0126] (1) Preparation of silane-modified antioxidant:
[0127] Weigh 100 parts of antioxidant 1135 and dissolve it in ethyl acetate. Weigh 0.07 parts of AlCl 3 The catalyst was stirred evenly, and 16 parts of acryloyl chloride was slowly added dropwise while stirring. After heating to 40°C for 2 hours, the pH was adjusted to neutral, washed with water, filtered, and vacuum dried to obtain the vinyl-terminated 1135. Weigh 100 parts of vinyl-terminated 1135, add 35 parts of ethyltriethoxysilane coupling agent, add 0.06 parts of chloroplatinic acid catalyst, heat to 75°C for 20 hours, and obtain silane-modified antioxidant 1135.
[0128] (2) Preparation of thermally conductive alumina powder modified by antioxidant 1135, i.e. preparation of thermally conductive powder modified by antioxidant:
[0129] Weigh 100 parts of unmodified alumina powder, dry them and place them in a high-speed disperser, weigh 2 parts of silane-modified antioxidant for pre-hydrolysis, and dissolve them in isopropanol to form an 80% solution, then slowly disperse the solution in the powder, heat to 70°C and react for 4 hours, then remove moisture, solvent, etc. in vacuo to obtain antioxidant-modified thermal conductive alumina powder.
[0130] (3) Preparation of isocyanate-terminated polyurethane prepolymer:
[0131] Take 30 parts of poly(hexamethylene dimer) diol with a molecular weight of 2000, heat to 110°C while stirring, keep vacuuming to remove water for 2 hours, cool to 40°C, fill with nitrogen, add 70 parts of liquefied MDI, slowly heat to 75°C, stir to react for 2 hours, and cool to room temperature to obtain a terminal isocyanate polyurethane prepolymer.
[0132] (4) Preparation of component A: 5 parts of castor oil polyol, 3 parts of bisphenol A polyether polyol, 7 parts of modified castor oil (Ito AC006), 85 parts of antioxidant modified thermal conductive aluminum hydroxide powder and 0.002 parts of dibutyltin dilaurate were mixed, dispersed and stirred evenly, and component A was obtained after stirring for 2 hours;
[0133] (5) Preparation of component B: 16 parts of isocyanate-terminated polyurethane prepolymer and 84 parts of antioxidant-modified thermal conductive alumina powder were mixed and stirred for 2 hours to obtain component B;
[0134] The aging-resistant, low-viscosity, high-thermal-conductivity polyurethane adhesive prepared in the above embodiment was used in combination at a volume ratio of 1:1 to test the mixed viscosity, tensile strength, shear strength, thermal conductivity of room-temperature curing, and shear strength after double 85 aging for 1000 hours. The substrates were untreated 6061 aluminum and PET.
[0135]
[0136] It can be seen from the data in the table that, compared with the thermal conductive powder modified by the ordinary method, the aging-resistant low-viscosity and high thermal conductive polyurethane adhesive of the present invention has a lower mixed viscosity, and the viscosity is reduced by 30%; the tensile strength and shear strength are greatly improved, and the shear strength is increased by 50%; the thermal conductivity is also slightly increased; the aging resistance is significantly improved, and the shear strength attenuation rate after double 85 aging for 1000h is reduced from more than 30% to less than 10%, which greatly ensures the long-term safety and extends the service life.
[0137] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims. The information disclosed in the background technology section of this article is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as an admission or in any form that the information constitutes prior art known to those skilled in the art.
Claims
1. An aging-resistant, low-viscosity, high-thermal-conductivity polyurethane adhesive, characterized in that: include: Component A and component B, wherein component A and component B are used in a volume ratio of 1:1, and the functional group molar ratio of component A to component B is: NCO:OH=1.02:1-2.0:1; The component A is made of the following materials in parts by mass: 0.1 to 15 parts of bio-based polyol, 0.1 to 5 parts of aromatic ring modified polyol, 0.1 to 10 parts of polyether polyol, 0.001 to 0.1 parts of catalyst, 0.1 to 5 parts of molecular sieve, 0.1 to 85 parts of common modified thermal conductive powder and 0.1 to 85 parts of antioxidant modified thermal conductive powder; The component B is made of the following components in parts by mass: 15-35 parts of terminal isocyanate polyurethane prepolymer, 0.1-1 part of water absorbent, 0.1-85 parts of common modified thermal conductive powder, 0-85 parts of antioxidant modified thermal conductive powder and 0.1-1 part of silane modified antioxidant.
2. The aging-resistant, low-viscosity, high-thermal-conductivity polyurethane adhesive according to claim 1, characterized in that: In the components A and B, the antioxidant modified thermal conductive powder is prepared in the following manner, and each component, by weight, comprises: Weigh 100 parts of unmodified thermal conductive powder, dry it and place it in a high-speed disperser; Weigh 100 parts of silane modified antioxidant for pre-hydrolysis and dissolve in a low boiling point solvent to prepare a solution with a mass concentration of 20-99%, then weigh 0.001-5 parts of the solution and slowly disperse it in the unmodified thermal conductive powder after high-speed dispersion, heat to 40-130°C and react for 0.1-12h, then remove the water and low boiling point solvent in vacuum to obtain the antioxidant modified thermal conductive powder.
3. The aging-resistant, low-viscosity, high-thermal-conductivity polyurethane adhesive according to claim 2, characterized in that: The low boiling point solvent is an alcohol solvent or an ester solvent, the alcohol solvent is any one of ethanol, methanol and isopropanol; the ester solvent is ethyl acetate.
4. The aging-resistant, low-viscosity, high-thermal-conductivity polyurethane adhesive according to claim 1 or 2, characterized in that: In the components A and B, the silane-modified antioxidant is prepared in the following manner, and each component, by weight, comprises: Weigh 100 parts of hindered phenol antioxidant, add 0.01-0.3 parts of Lewis acid catalyst, heat to 40-100°C, slowly drop acryloyl chloride, react for 1-12 hours until the reaction is finished, and obtain a vinyl-terminated antioxidant. Weigh the vinyl-terminated antioxidant according to the molar ratio of vinyl-terminated antioxidant: acryloyl chloride = 1.002-1.3, add alkyl silane coupling agent to the vinyl-terminated antioxidant, and then add 0.01-1000 ppm of platinum catalyst, react at 50-120°C for 5-48 hours to obtain a silane-modified antioxidant, in which the molar ratio of vinyl-terminated antioxidant: alkyl silane coupling agent = 1:0.9-1.
1.
5. The aging-resistant, low-viscosity, high-thermal-conductivity polyurethane adhesive according to claim 4, characterized in that: In the silane-modified antioxidant, the hindered phenol antioxidant is an antioxidant containing a phenol group; The Lewis acid catalyst is at least one of AlCl3, BF3, SbCl5, FeBr3, FeCl3, SnCl4, TiCl4, and ZnCl2; The alkylsilane coupling agent is one or more of a methylsilane coupling agent, an ethylsilane coupling agent, and an octylsilane coupling agent.
6. The aging-resistant, low-viscosity, high-thermal-conductivity polyurethane adhesive according to claim 5, characterized in that: The antioxidant containing a phenol group is any one of antioxidant 1076, antioxidant 1330, antioxidant 1135, antioxidant 2103 or a blend thereof.
7. The aging-resistant, low-viscosity, high-thermal-conductivity polyurethane adhesive according to any one of claims 1 to 3, characterized in that: In the component A, the bio-based polyol is castor oil, modified castor oil, soybean oil, modified soybean oil, cashew nut shell oil, cardanol polyol or a blend thereof, and has a molecular weight of 200 to 5000; The aromatic ring modified polyol is any one of aromatic ring modified polyether polyol, aromatic ring modified polyester polyol, aromatic ring modified bio-based polyol or a blend thereof, and has a molecular weight of 200 to 5000. The polyether polyol is any one of polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polypropylene glycol, or a blend thereof, and has a molecular weight of 200 to 5000; The catalyst is any one of bismuth isooctanoate, bismuth laurate, bismuth neodecanoate, bismuth naphthenate, zinc isooctanoate, zinc neodecanoate, dibutyltin, stannous octoate, chelated tin, or a blend thereof; The molecular sieve is any one of 3A molecular sieve activated powder, 4A molecular sieve activated powder, 5A molecular sieve activated powder or a blend thereof; The common modified thermal conductive powder material adopts any one of aluminum hydroxide, modified aluminum oxide, modified heavy calcium, modified calcium hydrogen, modified nano calcium, modified silicon micro powder or a blend thereof modified by a silane coupling agent or an esterification reaction.
8. The aging-resistant, low-viscosity, high-thermal-conductivity polyurethane adhesive according to any one of claims 1 to 3, characterized in that: In the B component, the terminal isocyanate polyurethane prepolymer is prepared in the following manner, and each component is measured by weight, including: heating the polyol to 110-130° C., stirring and evacuating, dehydrating for 1-3 hours, cooling to below 50° C., filling with nitrogen, adding isocyanate according to a ratio of 6-20% of the theoretical NCO content, heating to 65-85° C., stirring and reacting for 1-4 hours, until the titrated NCO content no longer changes, ending the reaction, and cooling to room temperature to obtain the terminal isocyanate polyurethane prepolymer.
9. The aging-resistant, low-viscosity, high-thermal-conductivity polyurethane adhesive according to claim 8, characterized in that: In the isocyanate-terminated polyurethane prepolymer, the polyol is any one of polyether polyol, polyester polyol, bio-based polyol or a blend thereof; The isocyanate may be any one of aliphatic isocyanate and aromatic isocyanate or a blend thereof.
10. A method for preparing the aging-resistant, low-viscosity, high-thermal-conductivity polyurethane adhesive according to any one of claims 1 to 9, characterized in that: include: Prepare component A and component B respectively; Preparation of component A: Take the raw materials used for component A according to the formula of claims 1-9; The bio-based polyol, aromatic ring modified polyol, polyether polyol, catalyst, molecular sieve, common modified thermal conductive powder and antioxidant modified thermal conductive powder in the raw materials of component A are mixed uniformly in a reaction kettle to obtain component A; Preparation of component B: Take the raw materials used for component B according to the formula of claims 1-9; The isocyanate-terminated polyurethane prepolymer, water absorbent, common modified thermal conductive powder, antioxidant modified thermal conductive powder and silane modified antioxidant in the raw materials of component B are mixed uniformly in a reaction kettle to obtain component B; The component A and the component B prepared above are used in a volume ratio of 1:1 to obtain an aging-resistant, low-viscosity, and high-thermal-conductivity polyurethane adhesive; The antioxidant modified thermal conductive powder used in the A component and the B component is prepared in the following manner, with each component being calculated by weight, comprising: weighing 100 parts of unmodified thermal conductive powder, drying it, and placing it in a high-speed disperser; Weigh 100 parts of silane modified antioxidant for pre-hydrolysis and dissolve in a low boiling point solvent to prepare a solution with a mass concentration of 20-99%, then weigh 0.001-5 parts of the solution and slowly disperse it in the unmodified thermal conductive powder, heat to 40-110° C. and react for 0.1-8 hours, then remove water and low boiling point solvent in vacuum to obtain antioxidant modified thermal conductive powder; The silane-modified antioxidant used in the A component and the B component is prepared in the following manner, and each component is measured by weight, including: weighing 100 parts of hindered phenol antioxidant, adding 0.01-0.3 parts of Lewis acid catalyst, heating to 40-100°C, slowly dropping acryloyl chloride, reacting for 1-8 hours until the reaction is finished, and obtaining a vinyl-terminated antioxidant, wherein the molar ratio of the vinyl-terminated antioxidant to acryloyl chloride is 1.002-1.
3. Weighing 100 parts of the vinyl-terminated antioxidant, adding an alkyl silane coupling agent to the vinyl-terminated antioxidant, and then adding 0.01-1000 ppm of platinum catalyst, reacting at 50-120°C for 5-48 hours, obtaining a silane-modified antioxidant, wherein the molar ratio of the vinyl-terminated antioxidant to the alkyl silane coupling agent is 1:0.9-1.1; The terminal isocyanate polyurethane prepolymer used in the B component is prepared in the following manner, with each component measured by weight, including: heating the polyol to 110-130° C., stirring and evacuating, dehydrating for 1-3 hours, cooling to below 50° C., filling with nitrogen, adding isocyanate at a ratio of 6-20% of the theoretical NCO content, heating to 65-85° C., stirring and reacting for 1-4 hours, until the titrated NCO content no longer changes, ending the reaction, and cooling to room temperature to obtain the terminal isocyanate polyurethane prepolymer.